The interface between multidisciplinary learning and digital transformation: Insights in higher education and healthcare in the 2021 century - Santos, Delba Fonseca; Cruz, Maria Jesus Barreto (Seven Editora, 2023)
The performance of universities and organizations in implementing the interface between multidisciplinary teaching and digital transformation is growing. This article sheds light on some relevant aspects of academic training on these two phenomena. Specifically, this work deals with insights between these areas to: 1) understand the connections between the themes and 2) identify gaps for advancement in the development of themes. This approach shows results from the literature on multidisciplinary work and digital transformation as key elements of changes in education and health systems. Quality health care responses depend on the engagement of different actors including educational institutions, teachers, students, policy makers and stakeholders. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-060